2014
DOI: 10.1586/1744666x.2014.958469
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of a historical cohort of Iranian common variable immunodeficiency patients

Abstract: Despite current efforts, more comprehensive studies are needed, especially for classification and investigation of the genetic background and prognostic factors for patients with CVID in order to better managment and followup of patinets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 93 publications
0
10
1
Order By: Relevance
“…Although this was the second most common infectious disease among Iranian XLA patients, chronic otitis media was the most common complication among chronic manifestations [35]. We found a lower rate of otitis media in CVID patients with hypogammaglobulinemia than in those with agammaglobulinemia [17,36]. This rate was higher in other studies [37][38][39], although this difference could be due to differences in the number of patients in each study (high in our study).…”
Section: Otitis Mediacontrasting
confidence: 57%
“…Although this was the second most common infectious disease among Iranian XLA patients, chronic otitis media was the most common complication among chronic manifestations [35]. We found a lower rate of otitis media in CVID patients with hypogammaglobulinemia than in those with agammaglobulinemia [17,36]. This rate was higher in other studies [37][38][39], although this difference could be due to differences in the number of patients in each study (high in our study).…”
Section: Otitis Mediacontrasting
confidence: 57%
“…+ T cells and that there is a strong correlation between naive CD4 + T-cell counts and clinical features [12,13,39,40]. In this regard, when CVID patients were classified on the basis of clinical phenotypes (infection only, polyclonal lymphoid proliferation, cytopenias, organ-specific autoimmunity, lymphoid malignancy, and enteropathy), the autoimmune cytopenia and organ-specific autoimmunity groups had the most significantly reduced naive CD4…”
Section: Naive Cd4 + T Cellsmentioning
confidence: 99%
“…In Iran, parental consanguinity is reported in 72% of patients suffering from CVID, while the mean proportion of consanguineous marriages in the country is 38% [35]. Previously, we also showed that the rate of parental consanguinity was significantly higher in children with early onset disease than in adults [9]. Furthermore, we have shown that the rate of multiple cases in a consanguineous cohort of CVID patients is more than 30% if all first relatives without severe clinical manifestations are evaluated [36].…”
Section: Discussionmentioning
confidence: 65%